Optimization of Gluten Free Bread Formulation by Adding Xanthan Gum, Potato Starch and Sorbitol Using Response Surface Methodology - Azwin, Ahmad; Mimi Sakinah, A. M.; S. Mohd, Ahmadi (Universiti Malaysia Pahang, 2016)
Gluten is a major component of some cereal and bakery product. Gluten can cause intestinal absorption problem especially to people who have celiac diseases. The aim of this research was to optimize a formulation of gluten free bread (GFB) based on rice flour. The target is to achieve high in volume and weight, but has minimum firmness value. A response surface methodology was used to analyze the amount of xanthan gum, potato starch and sorbitol based on physical properties of GFB.A Box-Behnken design with three independent variables and three levels was used to develop models for the different responses.The optimal formulation was 1.5g/100g xanthan gum, 40g/100g potato starch and 4.1/100g sorbitol, in rice flour basis. Three of breads were baked at the same time at optimum condition to validate the model. The optimize bread was found to be the best ranking of overall acceptance based on hedonic scale compared to the control bread at significant level p≤ 0.05, according to sensory evaluation. The results are useful in understanding the limitations amount of xanthan gum, potato starch, and sorbitol in order to produce a better quality of GFB.